Two‐Dimensional Covalent Organic Frameworks for Optoelectronics and Energy Storage. Issue 6 (29th May 2017) - Mandal, Amal Kumar; Mahmood, Javeed; Baek, Jong‐Beom
Abstract: Synthetic polymers with branched macromolecules and outstanding functional‐group tolerance exhibit diverse and useful properties that influence most aspects of modern life. Extending polymerization strategies to two dimensions (2D) allows precise integration of building units into extended structures with periodic skeletons and ordered nanopores. The construction principle of these frameworks is to direct the topological evolution in a predictable manner with controlled geometry, dimensions and structural periodicity. This unique designable feature of 2D covalent organic frameworks (2D‐COFs) with versatile properties makes them an emerging material platform, with great interest for areas such as gas storage, separation, catalysis and optoelectronics. In this Focus Review, we discuss the recent progress in 2D‐COFs as optoelectronic materials with an emphasis on their semiconducting, energy‐conversion and energy‐storage properties. Abstract : I've been framed : The unique designable features of 2D covalent organic frameworks (2D‐COFs) make them an emerging material platform with great potential for organic optoelectronics. In this Focus Review, the recent progress for 2D‐COFs as optoelectronic materials is discussed with an emphasis on their semiconducting, energy‐conversion and energy‐storage properties.